Methane dry reforming catalyst and preparation method thereof

The monolithic aerogel catalyst composed of Fe2O3, NiO, Al2O3, La2O3 and Gd2O3 solves the problems of easy sintering of active components and low mass transfer efficiency of oxygen support under high temperature cycling, and realizes a highly efficient methane dry reforming reaction. It has excellent cycle stability and low pressure drop performance and is suitable for industrial reactors.

CN121155604APending Publication Date: 2025-12-19LANZHOU RESOURCES & ENVIRONMENT VOC TECH COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511644576.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-11
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

In existing chemically chained methane dry reforming technologies, the active components of the oxygen carrier are prone to sintering under high-temperature cycling conditions, resulting in low microscopic mass transfer efficiency and poor macroscopic mechanical stability. Furthermore, the lack of effective coordination between material structure design and chemical chaining process requirements poses challenges to the scale-up design and long-term stable operation of the reactor.

Method used

A monolithic aerogel catalyst composed of Fe2O3, NiO, Al2O3, La2O3, and Gd2O3 was developed. Through precise active site design and material structure engineering, aerogel structures with honeycomb or mesh-like macroscopic morphologies were prepared. Fe-Ni bimetallic compounds were used as complementary active centers, and La-Gd composite rare earth elements were used as nano-welding agents. Combined with sol-gel monolithic molding and supercritical drying technology, the efficient synergy of active sites and structural stability were ensured.

Benefits of technology

It achieves high CH4/CO2 conversion and ideal H2/CO ratio, with excellent cycle stability and extremely low bed pressure drop. It solves the problems of rapid activity decline and insufficient mass transfer efficiency of traditional oxygen carriers under high temperature cycling, and meets the needs of industrial reactors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a methane dry reforming catalyst and a preparation method thereof, and belongs to the technical field of catalysts.The catalyst is composed of 480 parts to 600 parts of Fe2O3, 60 parts to 75 parts of NiO, 1020 parts to 1530 parts of Al2O3, 16.2 parts to 82.5 parts of La2O3 and 9 parts to 18 parts of Gd2O3, and the catalyst is of an integral aerogel structure with a honeycomb-shaped or latticed macroscopic morphology; the preparation method comprises the following steps: S1, preparing a precursor solution; s2, adding a gel accelerant; s3, carrying out integral gel forming; s4, aging the wet gel; s5, solvent replacement; s6, performing supercritical drying; s7, calcining; according to the invention, active site design, a structure stabilization strategy and material form innovation are closely combined, and the prepared monolithic aerogel oxygen carrier not only shows a high CH4 / CO2 conversion rate and an ideal H2 / CO ratio, but also has excellent cycle stability and extremely low bed pressure drop; the core problems that in the prior art, the activation capacity and the carbon removal capacity are not matched, the high-temperature cycling stability is poor, and the engineering applicability of a powder material is limited are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of catalysts, in particular to a methane dry reforming catalyst and a preparation method thereof. BACKGROUND

[0002] Methane dry reforming (referred to as DRM for short) technology can directly convert two main greenhouse gases CH4 and CO2 into synthesis gas (H2 and CO) with high economic value, which has both environmental protection and economic value in realizing carbon resource recycling and promoting the "double carbon" goal. In order to solve the core problem of deactivation of traditional catalysts due to carbon deposition and sintering, chemical looping methane dry reforming (referred to as CL-DRM for short) technology emerged as the times require. This technology uses metal oxide oxygen carriers to circulate between two reactors or reaction stages, which effectively inhibits the generation of carbon deposition in thermodynamics by splitting the traditional continuous reaction into alternating reduction and oxidation half-cycles, and realizes the internal separation and energy intensification of the reaction process, and is widely regarded as a potential solution to the deactivation problem of DRM catalysts.

[0003] However, the industrialization of CL-DRM technology is hindered by the lack of high-performance oxygen carriers. Existing oxygen carrier materials are mostly traditional granular or powdered metal oxides, which have the following limitations in actual application: First, poor cycle stability. Under the condition of high-temperature reduction-oxidation severe cycle, active metal components such as Ni and Fe are prone to migration, sintering and aggregation due to repeated expansion and contraction of the lattice, resulting in rapid decline in activity. At the same time, the structure of the carrier is also prone to collapse and densification during long-term cycling, further accelerating material deactivation. Second, insufficient mass transfer efficiency and reaction kinetics. In traditional granular packed fixed bed or fluidized bed reactors, the micro-pore structure of the oxygen carrier is usually not well developed, which limits the internal diffusion of the reaction gas and the outward diffusion of the product gas, thereby affecting the overall reaction rate and conversion efficiency. In addition, the engineering application performance is also not ideal: powdered oxygen carriers are prone to wear and powdering in fluidized beds, causing loss of active components and increasing system pressure drop; while in fixed beds, their packing form is prone to cause uneven heat transfer and local overheating, which poses a serious challenge to the scale-up design and long-term stable operation of the reactor.

[0004] Therefore, the development bottleneck of current CL-DRM technology is concentrated on how to construct an oxygen carrier material with high activity, high cycle stability and excellent engineering application form. The existing technical solutions cannot effectively coordinate between microstructure and macroform, resulting in that their process advantages are limited by the performance defects of the material itself and cannot be fully utilized.

[0005] Therefore, developing a new type of oxygen carrier capable of long-term stable operation under harsh chemical looping cycle conditions, while meeting the requirements of efficient mass and heat transfer and adapting to the needs of industrial reactors, has become a key technical requirement for promoting the large-scale industrial application of methane dry reforming technology. SUMMARY

[0006] The purpose of the present application is to provide a methane dry reforming catalyst and a preparation method thereof, in order to solve the technical problems in the prior art that the active components of the oxygen carrier are prone to sintering under high-temperature cycle conditions, the micro-mass transfer efficiency is low, the macro-mechanical stability is poor, and the material structure design lacks effective coordination with the chemical looping process requirements.

[0007] To achieve the above purpose, the present application provides the following solutions:

[0008] A methane dry reforming catalyst, the key is that the catalyst is composed of the following components: 480-600 parts of Fe2O3, 60-75 parts of NiO, 1020-1530 parts of Al2O3, 16.2-82.5 parts of La2O3, and 9-18 parts of Gd2O3; the catalyst is a monolithic aerogel structure with a honeycomb or grid macroscopic morphology.

[0009] Specifically, the mass ratio of Fe2O3 to NiO is (8.0-8.5):1.

[0010] Specifically, the mass ratio of La2O3 to Gd2O3 is (1.8-2.2):1.

[0011] A preparation method of the above-mentioned methane dry reforming catalyst, the key is that it comprises the following steps:

[0012] S1, precursor solution preparation: according to the mass fraction ratio, dissolve the metal nitrate of each component in deionized water to prepare a solution with a total metal ion concentration of 0.5-1.0 mol / L;

[0013] S2, gel promoter addition: add propylene oxide to the solution obtained in step S1 and stir;

[0014] S3, monolithic gel forming: pour the solution obtained in step S2 into a mold and stand at 40-60℃ to form a wet gel;

[0015] S4, wet gel aging: seal and age the wet gel obtained in step S3;

[0016] S5, solvent replacement: replace the solvent of the monolithic wet gel aged in step S4 with anhydrous ethanol;

[0017] S6, supercritical drying: the gel after solvent replacement in step S5 is subjected to supercritical CO2 drying to obtain an aerogel precursor;

[0018] S7, calcination:

[0019] First-stage calcination: the aerogel precursor obtained in step S6 is heated to 350-450 DEG C at a rate of 1-3 DEG C / min and kept for 1-3 h;

[0020] Second-stage calcination: the sample after the first-stage calcination is continuously heated to 600-750 DEG C at a rate of 2-5 DEG C / min and kept for 2-5 h;

[0021] S8, cooling: cooling to room temperature to obtain the methane dry reforming catalyst.

[0022] Further, in step S2, the molar ratio of propylene oxide to total metal ions is (5-7):1.

[0023] Further, the mold in step S3 is a honeycomb or grid mold.

[0024] Further, in step S4, the aging condition is sealed aging at 40-60 DEG C for 24-48 h.

[0025] Further, in step S5, the solvent replacement is replaced with anhydrous ethanol for 3-5 times, with an interval of 6-12 h.

[0026] Preferably, in step S6, the supercritical CO2 drying is carried out at a drying temperature of 40-50 DEG C, a drying pressure of 10-15 MPa, and a drying time of 2-4 h.

[0027] Preferably, the calcination process in step S7 is carried out in an air atmosphere.

[0028] The present application discloses the following technical effects:

[0029] The present application provides a kind of for chemical chain methane dry reforming monolithic aerogel oxygen carrier and preparation method thereof, by precise active site design and innovative material structure engineering combination, it has solved the technical bottleneck that traditional oxygen carrier is sintered in chemical chain cycle, carbon deposition is serious and engineering mass transfer is limited and lead to the performance rapid attenuation.For the composite catalyst technical route of different functional components compared with existing physical mixing, the present application provides a new material design and process path.Specific technical effects include:

[0030] First, the present application realizes the efficient synergistic effect of bifunctional active sites and structural stabilizers. In view of the problem that the existing oxygen carriers are difficult to balance the CH4 activation and CO2 carbon consumption capacity, and the deficiency that the double active sites in the traditional Ni-Mo composite catalyst are difficult to establish a stable balance, the present application adopts Fe-Ni bimetal as a complementary active center, and introduces La-Gd composite rare earth as a nano welding agent. The design provides lattice oxygen by Fe2O3 and activates CO2 at the same time, uses Ni to efficiently crack CH4, and extremely stabilizes the active site through the strong interaction of rare earth elements at the interface, so as to realize high reaction activity and excellent anti-sintering capacity at the same time in high temperature cycle.

[0031] Second, the catalyst of the present application has excellent anti-carbon deposition performance, which solves the core problem of carrier deactivation caused by carbon deposition in the chemical chain process. Different from the mechanism of carbon consumption after reaction by Mo-based components, the present application establishes an efficient carbon deposition-carbon consumption dynamic balance mechanism through the close cooperation of Fe-O and Ni active sites and the electronic regulation of La-Gd composite doping on the active center, which can timely migrate and oxidize the surface carbon species generated by the Ni site, so that the catalyst still maintains a very low carbon deposition amount after 50 cycles.

[0032] Third, the present application realizes the synergistic optimization of reaction performance and structural stability, breaks through the engineering limitations of the traditional composite catalyst powder mixing form, and through the macro-nano multi-level structure design of the monolithic aerogel, on the one hand, the three-dimensional through nano network ensures the efficient mass transfer of reaction gas and the full exposure of active sites; on the other hand, through the honeycomb / grid macro morphology, the material is endowed with excellent mechanical strength and structural integrity, solving the engineering bottleneck of easy wear and loss of powder catalyst in the cycle process.

[0033] Fourth, the present application realizes the optimization matching of microstructure and macro performance of the material through precise control of the key preparation process. In view of the problem that the traditional method is difficult to obtain high stability nano network structure, and the defect that the uniformity of multi-component mixing in the preparation of traditional composite catalyst is difficult to guarantee, the present application determines the process route of sol-gel monolithic molding combined with supercritical drying as the core, supplemented by programmed temperature calcination. The process effectively avoids the structure collapse caused by conventional drying, ensures the high dispersity of active components and the perfect preservation of the unique pore structure of aerogel, and provides guarantee for obtaining oxygen carriers with high activity and high stability.

[0034] In summary, the present application closely combines active site design, structure stabilization strategy and material morphology innovation, and the prepared monolithic aerogel oxygen carrier exhibits high CH4 / CO2 conversion rate and ideal H2 / CO ratio, and further has excellent cycle stability and extremely low bed pressure drop, effectively solving the core problems of mismatch between activation and carbon removal capacity, poor high-temperature cycle stability and limited engineering applicability of powder materials in the prior art. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present application will now be described in detail, which should be considered to be illustrative of certain aspects, features and embodiments of the present application and are not intended to limit the present application in any manner. Further, the detailed description should be considered in connection with the accompanying drawings.

[0036] It should be understood that the terms used in the present application merely describe particular embodiments and are not intended to limit the present application. In addition, for numerical ranges in the present application, it should be understood that each intermediate value between the upper limit and the lower limit of the range is also specifically disclosed. Each smaller range within any stated range or within any stated intermediate value is also included in the present application. The upper limit and the lower limit of these smaller ranges can be included or excluded independently.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application, preferred methods and materials are described. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials in connection with which the documents are cited. In case of conflict between the content of the specification and that of any document incorporated herein by reference, the content of the specification prevails.

[0038] Various modifications and changes can be made to the specific embodiments of the present application described herein without departing from the scope or spirit of the application. Other embodiments of the application will be apparent to those of ordinary skill in the art from the description and examples presented herein. The specification and examples given should be considered exemplary only.

[0039] As used herein, the terms “comprises”, “comprising”, “includes”, “including”, “has”, “having”, and the like are open-ended terms that are intended to denote the inclusion of elements or steps without excluding other elements or steps.

[0040] In each of the following examples and comparative examples, the composition of the catalyst is calculated in terms of the mass fraction of oxides in the final product; during preparation, each raw material is weighed according to the mass fraction of oxides converted into nitrate.

[0041] Example 1

[0042] The embodiment provides a methane dry reforming catalyst, which is a monolithic aerogel structure with a honeycomb macroscopic morphology; the catalyst is composed of the following components in mass fraction: 540 parts of Fe2O3, 65 parts of NiO, 1275 parts of Al2O3, 33 parts of La2O3 and 16.5 parts of Gd2O3; wherein the mass ratio of Fe2O3 to NiO is 8.31:1; and the mass ratio of La2O3 to Gd2O3 is 2.0:1.

[0043] The specific preparation process is as follows:

[0044] S1, preparation of a precursor solution:

[0045] According to the mass fraction of oxides, each raw material is weighed and converted into nitrate, Fe(NO3)3.9H2O, Ni(NO3)2.6H2O, Al(NO3)3.9H2O, La(NO3)3.6H2O and Gd(NO3)3.6H2O are dissolved in deionized water to prepare a solution with a total metal ion concentration of 0.75 mol / L;

[0046] S2, addition of a gel promoter:

[0047] Propylene oxide is added to the solution obtained in step S1 and stirred; wherein the molar ratio of propylene oxide to total metal ions is 6:1;

[0048] S3, monolithic gel forming:

[0049] The solution obtained in step S2 is poured into a honeycomb mold and placed at 50 DEG C to form a wet gel;

[0050] S4, aging of the wet gel:

[0051] The wet gel obtained in step S3 is sealed and aged at 50 DEG C for 36h;

[0052] S5, solvent replacement:

[0053] The monolithic wet gel aged in step S4 is subjected to 4 times of solvent replacement using anhydrous ethanol, and each time interval is 9h;

[0054] S6, supercritical drying:

[0055] The gel after solvent replacement in step S5 is subjected to supercritical CO2 drying, the drying temperature is controlled to be 45 DEG C, the drying pressure is controlled to be 12.5 MPa, and the drying time is controlled to be 3h, to obtain an aerogel precursor;

[0056] S7, calcination:

[0057] First-stage calcination is carried out in an air atmosphere: the aerogel precursor obtained in step S6 is heated to 400 DEG C at a rate of 2 DEG C / min and kept for 2h;

[0058] The second stage calcination was carried out under air atmosphere: the sample after the first stage calcination was continuously heated to 675℃ at a rate of 3.5℃ / min and kept for 2.5h;

[0059] S8, cooling:

[0060] cooling to room temperature to obtain the methane dry reforming catalyst, and the obtained catalyst is sample 1.

[0061] Example two

[0062] The present example provides a methane dry reforming catalyst, which is a monolithic aerogel structure with a honeycomb macroscopic morphology; the catalyst is composed of the following components in mass fraction: 480 parts of Fe2O3, 60 parts of NiO, 1530 parts of Al2O3, 16.2 parts of La2O3, and 9 parts of Gd2O3; wherein the mass ratio of Fe2O3 to NiO is 8.0:1; the mass ratio of La2O3 to Gd2O3 is 1.8:1.

[0063] The specific preparation process is as follows:

[0064] S1, preparation of precursor solution:

[0065] According to the mass fraction of oxides, each raw material is weighed and converted into nitrate, and Fe(NO3)3·9H2O, Ni(NO3)2·6H2O, Al(NO3)3·9H2O, La(NO3)3·6H2O and Gd(NO3)3·6H2O are dissolved in deionized water to prepare a solution with a total metal ion concentration of 0.5mol / L;

[0066] S2, addition of gel promoter:

[0067] Epoxy propane is added to the solution obtained in step S1 and stirred; wherein the molar ratio of epoxy propane to total metal ions is 5:1;

[0068] S3, monolithic gel forming:

[0069] The solution obtained in step S2 is poured into a honeycomb mold and placed at 40℃ to form a wet gel;

[0070] S4, aging of wet gel:

[0071] The wet gel obtained in step S3 is sealed and aged at 40℃ for 48h;

[0072] S5, solvent replacement:

[0073] The monolithic wet gel after aging in step S4 is subjected to 3 times of solvent replacement with anhydrous ethanol, with an interval of 12h each time;

[0074] S6, supercritical drying:

[0075] The gel after solvent replacement in step S5 is subjected to supercritical CO2 drying, with a drying temperature of 50°C, a drying pressure of 10 MPa, and a drying time of 2 h, to obtain an aerogel precursor;

[0076] S7, calcination:

[0077] The first-stage calcination is performed in an air atmosphere: the aerogel precursor obtained in step S6 is heated to 350°C at a rate of 1°C / min and held for 3 h;

[0078] The second-stage calcination is performed in an air atmosphere: the sample after the first-stage calcination is continuously heated to 600°C at a rate of 2°C / min and held for 5 h;

[0079] S8, cooling: cooling to room temperature to obtain the methane dry reforming catalyst, which is sample 2.

[0080] Example Three

[0081] The present example provides a methane dry reforming catalyst, which is a monolithic aerogel structure with a honeycomb macroscopic morphology; the catalyst is composed of the following components in mass fractions: 600 parts of Fe2O3, 75 parts of NiO, 1020 parts of Al2O3, 82.5 parts of La2O3, and 18 parts of Gd2O3; wherein the mass ratio of Fe2O3 to NiO is 8.5:1; and the mass ratio of La2O3 to Gd2O3 is 2.2:1.

[0082] The specific preparation process is as follows:

[0083] S1, preparation of a precursor solution:

[0084] The raw materials are weighed according to the oxide mass fraction ratio, and Fe(NO3)3·9H2O, Ni(NO3)2·6H2O, Al(NO3)3·9H2O, La(NO3)3·6H2O, and Gd(NO3)3·6H2O are dissolved in deionized water to prepare a solution with a total metal ion concentration of 1.0 mol / L;

[0085] S2, addition of a gel promoter:

[0086] Propylene oxide is added to the solution obtained in step S1 and stirred; wherein the molar ratio of propylene oxide to total metal ions is 7:1;

[0087] S3, monolithic gel molding:

[0088] The solution obtained in step S2 is poured into a honeycomb mold and left to form a wet gel at 60°C;

[0089] S4, aging of the wet gel:

[0090] The wet gel obtained in step S3 was sealed and aged at 60°C for 24 h;

[0091] S5, solvent replacement:

[0092] The monolithic wet gel after aging in step S4 was subjected to 5 times of solvent replacement with anhydrous ethanol, with an interval of 6 h;

[0093] S6, supercritical drying:

[0094] The gel after solvent replacement in step S5 was subjected to supercritical CO2 drying, with a drying temperature of 40°C, a drying pressure of 15 MPa, and a drying time of 4 h, to obtain an aerogel precursor;

[0095] S7, calcination:

[0096] First-stage calcination was performed in an air atmosphere: the aerogel precursor obtained in step S6 was heated to 450°C at a rate of 3°C / min and maintained for 1 h;

[0097] Second-stage calcination was performed in an air atmosphere: the sample after the first-stage calcination was continuously heated to 750°C at a rate of 5°C / min and maintained for 2 h;

[0098] S8, cooling:

[0099] Cooling to room temperature obtained the methane dry reforming catalyst, and the obtained catalyst was sample 3.

[0100] Example Four

[0101] This example provides a methane dry reforming catalyst, which is a monolithic aerogel structure with a grid-like macroscopic morphology; its component composition and specific preparation process are the same as those of Example One, and the only difference is that step S3 is performed in a grid-like mold. Cooling to room temperature obtained the methane dry reforming catalyst, and the obtained catalyst was sample 4.

[0102] Comparative Example One

[0103] This comparative example provides a methane dry reforming catalyst, and the specific implementation is the same as that of Example One, with the difference being that the addition of Fe elements is completely removed. In mass parts, the catalyst is composed of the following components: 65 parts of NiO, 1275 parts of Al2O3, 33 parts of La2O3, and 16.5 parts of Gd2O3; wherein the mass ratio of La2O3 to Gd2O3 is 2.0:1. The specific preparation process of the catalyst is the same as that of Example One, with the difference being that no iron salt is added when the precursor solution is prepared. The obtained catalyst is denoted as Comparative Sample 1.

[0104] Comparative Example Two

[0105] The comparative example 1 provides a methane dry reforming catalyst, the specific implementation is the same as example 1, the difference is that the La and Gd rare earth elements are completely removed, and the catalyst is composed of the following components in mass fraction: 540 parts of Fe2O3, 65 parts of NiO, 1275 parts of Al2O3; wherein the mass ratio of Fe2O3 to NiO is 8.31:1. The specific preparation process of the catalyst is the same as example 1, the difference is that no rare earth element is added when the precursor solution is prepared, and the obtained catalyst is recorded as comparative product 2.

[0106] Comparative example 3

[0107] The comparative example 1 provides a methane dry reforming catalyst, the specific implementation is the same as example 1, the difference is that the La and Gd rare earth elements are completely removed, and the catalyst is composed of the following components in mass fraction: 540 parts of Fe2O3, 65 parts of NiO, 1275 parts of Al2O3; wherein the mass ratio of Fe2O3 to NiO is 8.31:1. The specific preparation process of the catalyst is the same as example 1, the difference is that no rare earth element is added when the precursor solution is prepared, and the obtained catalyst is recorded as comparative product 2.

[0108] Comparative example 4

[0109] The comparative example 1 provides a methane dry reforming catalyst, the specific implementation is the same as example 1, the difference is that the La and Gd rare earth elements are completely removed, and the catalyst is composed of the following components in mass fraction: 540 parts of Fe2O3, 65 parts of NiO, 1275 parts of Al2O3; wherein the mass ratio of Fe2O3 to NiO is 8.31:1. The specific preparation process of the catalyst is the same as example 1, the difference is that no rare earth element is added when the precursor solution is prepared, and the obtained catalyst is recorded as comparative product 2.

[0110] The specific preparation process is:

[0111] S1, preparation of precursor solution: the same as step S1 of example 1;

[0112] S2, addition of gel promoter: the same as step S2 of example 1;

[0113] S3, shaping of monolithic gel:

[0114] Pour the solution obtained in step S2 into an open petri dish and stand at 50℃ to form a block-shaped wet gel;

[0115] S4, aging of wet gel: the same as step S4 of example 1;

[0116] S5, solvent replacement: the same as step S5 of example 1;

[0117] S6, normal pressure drying:

[0118] Place the wet gel after solvent replacement in step S5 in a forced air drying oven and dry at 80℃ for 24h to obtain a dry gel block;

[0119] S7, grinding and shaping:

[0120] The dried xerogel block was ground into fine powder, then pressed into tablets using a tablet press at a pressure of 10 MPa, and then broken and sieved to obtain particles of 40-60 mesh.

[0121] S8, calcination: same as step S7 of Example 1;

[0122] S9, cooling: same as step S8 of Example 1, and the obtained catalyst is denoted as Control 4.

[0123] Analysis and testing

[0124] The samples 1-4 prepared in Examples 1-4 and the controls 1-4 prepared in Comparative Examples 1-4 were subjected to chemical looping methane dry reforming performance testing; all tests were performed in the same micro fixed bed reactor, and the testing process followed the laboratory standard specification.

[0125] I. CL-DRM reaction activity and selectivity testing

[0126] The test was performed at a reaction temperature of 675°C, atmospheric pressure, and using 0.2 g of catalyst sample or control. Each cycle included a reduction half-cycle (20% CH4 / Ar was introduced for 5 min) and an oxidation half-cycle (20% CO2 / Ar was introduced for 5 min). Data from the 10th cycle steady state were taken to calculate CH4 conversion, CO2 conversion, and syngas H2 / CO ratio. The test results are shown in Table 1.

[0127] Table 1: CL-DRM reaction activity and selectivity test results

[0128]

[0129] As can be seen from the results in Table 1, the samples 1-4 prepared in the examples of the present application exhibit stable and efficient CH4 and CO2 conversion in the CL-DRM reaction, and the H2 / CO ratio is close to the ideal value of 1:1. This is because of the synergistic effect of the Fe-Ni bimetal of the present application, in which the Ni site efficiently cracks CH4, and the adjacent Fe oxygen carrier site provides lattice oxygen in time to eliminate surface carbon species and activates CO2.

[0130] The control sample 1 has a significantly reduced CO2 activation ability due to the complete absence of Fe element as oxygen carrier, resulting in severe carbon deposition and limited CH4 conversion rate. The control sample 2 has the lowest CH4 conversion rate due to the absence of La and Gd elements for stabilization, and the active sites may have been sintered at the initial stage of the test. The control sample 3 uses Ce instead of Gd, and the electronic stabilization effect is weaker, so the activity and stability are between the examples and other control samples. The control sample 4 uses a traditional powder catalyst, which has poor mass transfer efficiency, resulting in insufficient contact between the reactants and active sites, and the activity is significantly lower than that of the monolithic aerogel of the present application.

[0131] II. Test of cycle stability and anti-carbon deposition performance

[0132] The samples and control samples were subjected to 50 consecutive CL-DRM cycles (total reaction time of 500 min) under the same conditions. The stability was evaluated by comparing the decrease in CH4 conversion rate and CO2 conversion rate between the 50th cycle and the 10th cycle.

[0133] After the reaction, the amount of carbon deposition (in mass percentage) was determined by thermogravimetric analysis. The test results are shown in Table 2.

[0134] Table 2: Test results of cycle stability and anti-carbon deposition performance

[0135]

[0136] As can be seen from the results in Table 2, the samples 1-4 prepared in the examples of the present application exhibit good cycle stability, not only the decrease in CH4 and CO2 conversion rates is small, but also the amount of carbon deposition is extremely low. This proves that the Fe-Ni bifunctional sites can effectively maintain the ability of Ni sites to continuously activate CH4 and the ability of Fe sites to activate CO2 and provide carbon-removing lattice oxygen simultaneously stable in long-term cycles. At the same time, the composite doping of La2O3 and Gd2O3 effectively inhibits the sintering of active sites, and the three-dimensional nanometer network of monolithic aerogel ensures efficient transport of reactants and products, which together ensures stable reaction cycles.

[0137] In contrast, the CH4 and CO2 conversion rates of all the control samples decrease significantly, and carbon deposition is severe. The control sample 1 has the most significant decrease in CO2 conversion rate due to the complete absence of Fe oxygen carrier, which destroys the CO2 activation and carbon removal path, and the decrease in CO2 conversion rate is even slightly higher than that of CH4 conversion rate. The control sample 2 has the most significant decrease in CH4 activation ability due to the absence of rare earth stabilizers, resulting in severe sintering of active sites. The control sample 3 uses Ce instead of Gd, which reduces the stabilization effect and leads to a decrease in the stability of the bifunctional sites. The control sample 4 has severe carbon deposition due to poor mass transfer efficiency, which simultaneously hinders the contact between CH4 and CO2 and active sites, resulting in a significant decrease in both conversion rates.

[0138] III. Pressure drop and mechanical strength test

[0139] In a 10mm diameter reactor tube, 1.0g of catalyst was filled, and the bed pressure drop was measured at a nitrogen flow rate of 100mL / min; meanwhile, the mechanical strength of the monolithic catalyst was measured by lateral compression experiment. The test results are shown in Table 3.

[0140] Table 3: Test results of engineering application performance

[0141]

[0142] As can be seen from the results in Table 3, the monolithic aerogel catalyst samples 1-4 of the present application all exhibit extremely low bed pressure drop and good mechanical strength. This is because the samples of the present application have regular honeycomb / grid macro-pores, which provide a smooth path for the gas flow, and the aerogel itself has a certain skeletal strength.

[0143] The bed pressure drop of the powder catalyst control sample 4 is more than 15 times that of the monolithic samples of the present application, and there is a risk of elutriation under the impact of the gas flow. This fully proves the engineering advantages of the monolithic aerogel structure in achieving low pressure drop and avoiding material loss.

[0144] However, the difference in composition will also affect the mechanical strength of the material to some extent. The mechanical strength of control sample 1 decreases significantly, indicating that the introduction of Fe not only serves as an active site, but also as a structural enhancer, which cooperates with the Al2O3 skeleton to improve the integrity of the material. The mechanical strength of control sample 2, which lacks rare earth elements, is the worst, proving that the composite rare earth as a nano solder plays a crucial role in strengthening the aerogel network and preventing it from breaking under stress. The mechanical strength of control sample 3 is between that of the samples of the present application and control sample 2, indicating that the Gd element used in the present application is superior to the Ce element in enhancing the structural stability.

[0145] In summary, the present application combines ingenious component design with innovative monolithic aerogel material structure to prepare a chemical looping methane dry reforming oxygen carrier that has high activity, high selectivity, excellent stability, excellent anti-coking ability and good engineering application performance, and the comprehensive performance is superior to that of the prior art, providing an effective solution to the problems of DRM catalyst deactivation and process intensification.

[0146] The above-described embodiments are only preferred modes of the present application, and do not limit the scope of the present application. Without departing from the design spirit of the present application, various modifications and improvements to the technical solutions of the present application made by those skilled in the art shall fall within the protection scope of the present application as defined by the claims.

Claims

1. A methane dry reforming catalyst, characterized in that, The catalyst is composed of the following components: 480 to 600 parts of Fe2O3, 60 to 75 parts of NiO, 1020 to 1530 parts of Al2O3, 16.2 to 82.5 parts of La2O3, and 9 to 18 parts of Gd2O3; the catalyst is an integral aerogel structure with a honeycomb or mesh-like macroscopic morphology.

2. The methane dry reforming catalyst according to claim 1, characterized in that, The mass ratio of Fe2O3 to NiO is (8.0~8.5):

1.

3. The methane dry reforming catalyst according to claim 1, characterized in that, The mass ratio of La2O3 to Gd2O3 is (1.8~2.2):

1.

4. A method for preparing a methane dry reforming catalyst as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Preparation of precursor solution: Dissolve the metal nitrates of each component in deionized water according to the mass ratio to prepare a solution with a total metal ion concentration of 0.5 mol / L to 1.0 mol / L. S2, Addition of gelation accelerator: Add propylene oxide to the solution obtained in step S1 and stir; S3, Integral gel molding: Pour the solution obtained in step S2 into a mold and let it stand at 40℃~60℃ to form a wet gel; S4. Aging of wet gel: The wet gel obtained in step S3 is sealed and aged. S5, Solvent replacement: The monolithic wet gel aged in step S4 is replaced with anhydrous ethanol. S6. Supercritical drying: The gel after solvent replacement in step S5 is dried with supercritical CO2 to obtain the aerogel precursor. S7, Calcination: First stage calcination: The aerogel precursor obtained in step S6 is heated to 350℃~450℃ at a rate of 1℃ / min~3℃ / min and held at that temperature for 1h~3h. Second stage calcination: The sample after the first stage calcination treatment is heated to 600℃~750℃ at a rate of 2℃ / min~5℃ / min and held for 2h~5h. S8. Cooling: Cool to room temperature to obtain the methane dry reforming catalyst.

5. The preparation method according to claim 4, characterized in that, In step S2, the molar ratio of propylene oxide to total metal ions is (5-7):

1.

6. The preparation method according to claim 4, characterized in that, The mold in step S3 is a honeycomb or mesh mold.

7. The preparation method according to claim 4, characterized in that, In step S4, the aging conditions are sealed aging at 40℃~60℃ for 24h~48h.

8. The preparation method according to claim 4, characterized in that, In step S5, solvent replacement is performed by replacing with anhydrous ethanol 3 to 5 times, with an interval of 6 to 12 hours between each replacement.

9. The preparation method according to claim 4, characterized in that, In step S6, the conditions for supercritical CO2 drying are: drying temperature 40℃~50℃, drying pressure 10MPa~15MPa, and drying time 2h~4h.

10. The preparation method according to claim 4, characterized in that, The calcination process in step S7 is carried out in an air atmosphere.